A Generalization of a Cobweb Theorem - Manning, R. (Review of Economic Studies, 1971)
Journal Article A Generalization of a Cobweb Theorem Get access R. Manning R. Manning La Trobe University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 1, January 1971, Pages 123–125, https://doi.org/10.2307/2296631 Published: 01 January 1971